The Marital Satisfaction of Differently-Aged Couples - Wang-Sheng Lee; Terra McKinnish (Global Labor Organization (GLO), 2017)
We investigate how the marital age gap affects the evolution of marital satisfaction over the duration of marriage using household panel data from Australia. We find that men tend to be more satisfied with younger wives and less satisfied with older wives. Interestingly, women likewise tend to be more satisfied with younger husbands and less satisfied with older husbands. Marital satisfaction declines with marital duration for both men and women in differently-aged couples relative to those in similarly-aged couples. These relative declines erase the initial higher levels of marital satisfaction experienced by men married to younger wives and women married to younger husbands within 6 to 10 years of marriage. A possible mechanism is that differently-aged couples are less resilient to negative shocks compared to similarly-aged couples, which we find some supportive evidence for.
Keywords: D1; J12; 330; assortative matching; marital age gap; marital duration; marital satisfaction